2011
DOI: 10.1111/j.1365-2516.2011.02700.x
|View full text |Cite
|
Sign up to set email alerts
|

F8 and F9 mutations in US haemophilia patients: correlation with history of inhibitor and race/ethnicity

Abstract: Both genetic and treatment-related risk factors contribute to the development of inhibitors in haemophilia. An inhibitor surveillance system piloted at 12 US sites has the goal of assessing risk factors through prospective data collection. This report examines the relationship of genotype and race/ethnicity to history of inhibitor in a large cohort of US haemophilia patients. Mutation analysis was performed on 676 haemophilia A (HA) and 153 haemophilia B (HB) patients by sequencing, Multiplex Ligation-dependen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
103
2
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 112 publications
(118 citation statements)
references
References 28 publications
12
103
2
1
Order By: Relevance
“…This F9 mutation has been identified previously in other patients with mild haemophilia B [4] and appears to be more common in the African American population. Of note, the liver donor was a 14-yearold African American male who died of a subdural haematoma after a fall.…”
supporting
confidence: 62%
“…This F9 mutation has been identified previously in other patients with mild haemophilia B [4] and appears to be more common in the African American population. Of note, the liver donor was a 14-yearold African American male who died of a subdural haematoma after a fall.…”
supporting
confidence: 62%
“…The hypothesis that mismatches in the sequences due to some polymorphisms could be the cause of a higher incidence of nADAs among African-American patients [16,28,30] has however, not been experimentally verified and the underlying mechanism for this clinical observation are not understood. The study is also controversial as a similar correlation between sequence mismatch due to polymorphisms and increased prevalence of nADAs has not been observed in two additional studies [31,32].…”
Section: Underlying Polymorphisms Sequence Mismatch Peptide-mhc Affmentioning
confidence: 96%
“…In contrast to these observations, other recent studies have not found any statistical association between F8 polymorphisms and inhibitor incidence [32][33][34]. One such study sought to determine whether African American patients with hemophilia A and inhibitor have FVIII-specific T cells that are able to distinguish between normal FVIII concentrates and FVIII peptides carrying alternative ns-SNPs [34].…”
Section: Fviii Polymorphisms and Fviii-specific T Cellsmentioning
confidence: 97%